Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/aob/mcw040
|View full text |Cite
|
Sign up to set email alerts
|

Light-dependent activation of phosphoenolpyruvate carboxylase by reversible phosphorylation in cluster roots of white lupin plants: diurnal control in response to photosynthate supply

Abstract: Background and Aims Phosphoenolpyruvate carboxylase (PEPC) is a tightly regulated enzyme that controls carbohydrate partitioning to organic acid anions (malate, citrate) excreted in copious amounts by cluster roots of inorganic phosphate (Pi)-deprived white lupin plants. Excreted malate and citrate solubilize otherwise inaccessible sources of mineralized soil Pi for plant uptake. The aim of this study was to test the hypotheses that (1) PEPC is post-translationally activated by reversible phosphorylation in cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…Exudation of malate and citrate was strongly stimulated under 0 μM P, as reported for other species bearing cluster roots when growing under low-P conditions ( Shane et al, 2004c ; Delgado et al, 2014 ), and citrate was exuded relatively more than other carboxylates ( Supplementary Table S1 ). A possible explanation is that substantial exudation of citrate and malate, especially citrate, has been linked to increased biosynthesis and decreased metabolism of citrate in the tricarboxylic acid cycle ( Neumann et al, 1999 , 2000 ; Shane et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exudation of malate and citrate was strongly stimulated under 0 μM P, as reported for other species bearing cluster roots when growing under low-P conditions ( Shane et al, 2004c ; Delgado et al, 2014 ), and citrate was exuded relatively more than other carboxylates ( Supplementary Table S1 ). A possible explanation is that substantial exudation of citrate and malate, especially citrate, has been linked to increased biosynthesis and decreased metabolism of citrate in the tricarboxylic acid cycle ( Neumann et al, 1999 , 2000 ; Shane et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an aside, a correlative relationship between Suc, Tre6P, and the posttranslational activation status of PEPC has also recently been reported in cluster roots of white lupin (Lupinus albus), which synthesizes organic acids in the roots and exudes them into the rhizosphere to mobilize Pi, iron, and other nutrients for uptake by the roots (Shane et al, 2016). White lupin root exudates can represent up to 25% of the plant's overall C budget, and it was suggested that Tre6P links the activation status of PEPC and anaplerotic synthesis of organic acids in the roots to the supply of Suc from the source leaves.…”
Section: Tre6p Regulates Photoassimilate Partitioning In Leaves Durinmentioning
confidence: 92%
“…A–D). Cluster roots are strong photosynthate sinks that excrete copious amounts of sucrose‐derived organic anions into the surrounding rhizosphere to solubilize otherwise inaccessible sources of mineralized soil P i for plant uptake . We also detected p41 protein‐staining polypeptides of varying intensities following anti‐RcSUS1 co‐IPs of developing sunflower, pine, and maize seed extracts (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Castor ( R. communis ; cv Baker 296), white lupin ( Lupinus albus ), and Harsh Hakea ( Hakea prostrata ) plants were cultivated in a greenhouse as previously described . Developing sweet corn ( Zea mays ) cobs and sunflower ( Helianthus annuus ) heads were collected in mid‐August from intact plants cultivated outdoors at Forman Farms near Seeley's Bay, Ontario, Canada.…”
Section: Methodsmentioning
confidence: 99%